The Geographical and Administrative Landscape of Lower Middle Egypt in Text B of the Wilbour Papyrus - Antoine, Jean Christophe (Zeitschrift für ägyptische Sprache und Altertumskunde, 2017)
The geographical information contained in text B of P. Wilbour has not been fully exploited. Completing text A, they suggest that the Memphite administration conducted the land surveys recorded in the papyrus with the consequence that the 17 th and 20 th Nomes of Upper Egypt (encompassing at that time the 18 th , 19 th , 21 th and 22 th Nomes) were probably administratively attached to Lower Egypt. It was also possible to propose the identification of Ope ( ʾIpt ) with modern Biba, P-Tjesy-Haur ( P Ꜣ -ṯsy-Ḥur ) with Saft Meidum and Onayna (ꜤꜢ n Ꜣ yn Ꜣ) with Greek Οννη, while Su ( Sw ) may have been located in the vicinity of Kiman al-Arus. Furthermore, W-ḥry-ı͗b , the Middle Country, as ʾIw-ḥry-ı͗b of the contending of Horus and Seth, probably designated a part of the valley comprised between the Nile and a perennial or seasonal and probably discontinuous waterway running in the central part of the floodplain from the Herakleopolite Nome to the region of Neferusi in the 16th Nome.